MODERNITY IN THE FRAME OF MULLAH AUTHORITIES IN DAUDI BOHRA DENOMINATION - E. ZAENAL MUTTAQIN (Al Qalam, 2011)
Daudi Bohras as a prominent Shiite Ismaili sect in India has been recognized as a modern Islamic society. Despite their traditional Islamic Shiite custom which is brought up from their ancestry, yet the people of Bohras has a distinct perspective toward Islam as the way of life. Unlike the other Shiite sects that put themselves on a distance to the modernity, Bohras people are able to cooperate within the modern issues in the frame of traditional. Mullah, or Da'i Mutlaq played an important role as a top cleric leader in guiding his people according to their rules. Indeed, Da'i Mutlaq, who is recognized as a representative of imam (leader of Shiite Islam), has successfully combined the outlook of his people in defining Islam in their cultural frame. Therefore, it is an intriguing phenomenon to be observed This paper is, as a matter of fact, Jonah Blanks anthropological work used as a main reference. Keywords: Daudi Bohra, Shiite, India